Pengembangan Atraksi Wisata Petirtaan Jolotundo Di Desa Seloliman, Trawas, Mojokerto - Riris Yuniarsih (PolimdoSains, 2019)
Jolotundo Petirtaan Seloliman village, Trawas, Mojokerto is a tourist attraction located on the mountain slope. There has not been a significant increase in development due to the fact that it is still known for the locals and there is no public transportation and promotion has been done properly. The purpose of the study was to explain the development of the tourist attraction of Petirtaan Jolotundo Trawas which has high potentials for variou toruist attraction. The method used in this research is descriptive qualitative method with data collection techniques of observation, interviews and documentation. The results of this study recommend the addition of facilities and infrastructure to develop Jolotundo Petirtaan tourism attractions such as public transportation to Jolotundo Petirta, the need for bus settle as a tour package from tourism objects in Trawas such as bus settle starting from Ngoro Stop, Petolaan Jolotundo, Lanang Statue Men), Arca wadok (Women), Glass Statues (Mirrors), Dlundung waterfalls, organic acrobusiness farms (tourist villages), home stays, trawas shelters. This tour package can be done otherwise and promotions both online and offline are made that can reach national and international marketing.